Activated Carbon from Sugarcane (Saccharum officinarum L.) Bagasse for Removal Ca2+ and Mg2+ Ion from Well Water - Ira Tyas Kurniasari; Cucun Alep Riyanto; Yohanes Martono (Stannum : Jurnal Sains dan Terapan Kimia, 2020)
Humans need water with good quality to fulfill their needs. Water with high hardness content will have a bad impact if consumed continuously, so the adsorption method is carried out to reduce the concentration of Ca2+ and Mg2+ ions. The adsorption process uses sugarcane bagasse activated carbon (SBAC) and the tested water sample is well water in District Jati, Kudus. Synthesis of SBAC was conducted with H3PO4 30% as an activator at an impregnation ratio of 1:5 (w/w) at temperature 700°C. The FTIR result showed that SBAC contains O-H, C-H, C=C, C≡C, and C-O as functional groups. Analysis result with the XRD instrument showed that the microstructure of SBAC that is formed is turbostatic structure and amorphous. Modeling isotherm suitable for SBAC adsorption on Ca2+ ions is Langmuir isotherm where the R2 value is 0.9134 which shows that the adsorption process occurs chemically and monolayer. Modeling isotherm suitable for SBAC adsorption on Mg2+ ions is Elovich isotherm where the R2 value is 0.8638 which means that the adsorption process is multilayer and adsorption in non-ideal conditions. Modeling kinetics suitable for SBAC adsorption on Ca2+ and Mg2+ ions is Pseudo Orde 2 where the R2 value is 0.9395 and 0.7274. Percent efficiency value of sugarcane activated carbon adsorption of Ca2+ dan Mg2+ ions on District Jati, Kudus well water is 14.44% and 8.94% and 40 minutes stirring time.